(untitled) (Research, Society and Development, 2025)
This work aims to address, through a literature review, the therapeutic use of cannabis in veterinary medicine, highlighting its benefits, risks, side effects and legal advances. Cannabis is a plant with numerous therapeutic benefits, used to treat chronic, neuropathic, inflammatory, oncological pain, glaucoma, and epilepsy. Therefore, proper management of these derivatives can alleviate pain and anxiety, providing comfort and well-being to animals. The use of these derivatives reduces the cost of other medications. Despite the proven benefits in research, the use of cannabis in veterinary medicine still faces legal obstacles, especially in Brazil, where specific regulations are lacking. This limits research development and investment from the pharmaceutical industry. The literature highlights the therapeutic potential of CBD for various conditions, such as chronic pain, osteoarthritis, chemotherapy-induced nausea, and neurological diseases, with few or no side effects when administered correctly. The methodology used in this research was a qualitative literature review, with data collected from scientific and institutional platforms. Analysis of the studies indicates that cannabis may be a promising and safe alternative for veterinary treatments, provided it is supervised by qualified professionals and supported by appropriate legal regulations.